(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this article, the concept of a mapping contracting perimeter of triangles embedded with F-contractions in the framework of b-metric spaces is introduced. Some related fixed point results are established. Banach Contraction Principle is derived as a corollary of main result. Additionally, we construct examples of mappings contracting perimeters of triangles embedded with F-contractions which are not contraction mappings in the framework of b-metric spaces. The results of this article are the extensions of some already established results in literature